2005
DOI: 10.1002/fedr.200411072
|View full text |Cite
|
Sign up to set email alerts
|

The vegetation of mining dumps in SW‐Sardinia

Abstract: The vegetation of mining dumps of SW-Sardinia includes\ud several endemic or rare species, that have\ud been confined to such artificial habitats by a millennial\ud mining activity. The extreme edaphic specialization\ud of these species reflects with unusual fidelity the\ud heterogeneity of substrata, therefore creating a system\ud of plant communities that largely contributes to\ud the environmental diversity of this part of the island.\ud The phytosociological study presented in this paper\ud recognized eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 10 publications
1
36
0
Order By: Relevance
“…In the field the first fungal species was associated with roots of Ammophila arenaria (L.) Link and an unrecognized plant species colonizing dunes of the Mediterranean Sea belonging to Greece and Spain, respectively, and the second fungus formed mycorrhiza with a Cistum sp. (Cistaceae) growing in Italy in soil highly acidified and contaminated with heavy metals (Angioloni et al 2005). Subsequent phylogenetic analyses of sequences spanning the small subunit (SSU, partial) gene, the internal transcribed spacer (ITS1, 5.8S, ITS2, full) and the large subunit (LSU, partial) nrDNA gene, named here SSU-ITS-LSU, and morphological studies of spores and mycorrhizae confirmed our supposition and placed both fungi among Septoglomus spp.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the field the first fungal species was associated with roots of Ammophila arenaria (L.) Link and an unrecognized plant species colonizing dunes of the Mediterranean Sea belonging to Greece and Spain, respectively, and the second fungus formed mycorrhiza with a Cistum sp. (Cistaceae) growing in Italy in soil highly acidified and contaminated with heavy metals (Angioloni et al 2005). Subsequent phylogenetic analyses of sequences spanning the small subunit (SSU, partial) gene, the internal transcribed spacer (ITS1, 5.8S, ITS2, full) and the large subunit (LSU, partial) nrDNA gene, named here SSU-ITS-LSU, and morphological studies of spores and mycorrhizae confirmed our supposition and placed both fungi among Septoglomus spp.…”
Section: Introductionsupporting
confidence: 60%
“…Spores of S. turnauae were isolated from one pot trap culture inoculated with the rhizosphere soil and root fragments of a Cistus sp. growing in a mine with soil highly acidified and contaminated with heavy metals (Angioloni et al 2005). This mine is located in SulcisIglesiente, SW-Sardinia, Italy (39°28′51″N, 8°28′51″E; altitude 384.20 m).…”
Section: Taxonomymentioning
confidence: 99%
“…The plant selection was based on previous field studies related to geobotanical aspects of SW-Sardinia mining areas [2,3,4] and was directed to choose metal tolerant plants which develop enough biomass to decontaminate the soil in acceptable times. Three little shrub species that often occur on contaminated substrata were selected.…”
Section: Plant Selectionmentioning
confidence: 99%
“…This plant is a shrub, 25-40 cm in height, strongly aromatic, with linear leaves, the lower not longer than 12 mm; the flowers are grouped in yellow heads and fruits are brown achenes 1 . It is used in Sardinian traditional medicine to nurse cough, burns and as antirheumatic and analgesic 2 .…”
Section: Introductionmentioning
confidence: 99%